A clinical study of the piezosurgery, high-speed contra-angle handpiece, and the combined application of both for extraction of embedded supernumerary teeth - Maihepireti Maihemaiti; Ailimaierdan Ainiwaer; Ling Wang (BMC, 2023)
Abstract Objectives To compare the effectiveness of three methods: high-speed contra-angle handpiece (HSCAH), piezosurgery, and combined in the extraction of different locations and types of embedded supernumerary teeth. Methods Sixty cases with different locations and different types of embedded supernumerary teeth were randomly divided into three groups for extraction by HSCAH, piezosurgery, and the combination of both, and the intraoperative and postoperative conditions of the three groups were compared and analyzed. Results In the extraction of embedded supernumerary teeth in the inverted, horizontal, and root tip positions, the piezosurgery group required significantly longer operative time and reduced intraoperative bleeding compared with the HSCAH and the piezosurgery combined with the HSCAH; it could effectively relieve postoperative pain and facial swelling. In the extraction of oblique, orthodontic, middle, and crown segments of embedded supernumerary teeth, the use of a piezosurgery combined with an HSCAH can effectively reduce the operative time, while the factors of bleeding, postoperative pain, and facial swelling not statistically significant when compared with a piezosurgery. Compared with the HSCAH and combined piezosurgery, piezosurgery can significantly reduce the fear of patients. Conclusion Piezosurgery is effective in extracting embedded supernumerary teeth in inverted, horizontal, and apical positions, effectively reducing intraoperative and postoperative trauma and shortening the time required for healing. The piezosurgery combined with an HSCAH can effectively reduce intraoperative and postoperative trauma when extracting embedded supernumerary teeth in oblique, orthodontic, middle, and crown positions. piezosurgery is a technique suitable for the treatment of patients with fear.